1977
DOI: 10.1080/10862967709547201
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Processes in Beginning Reading

Abstract: Abstract. A presentation is given of a strategic-process perspective on the development of reading skills. The approach integrates reading research with developmental findings in cognitive psychology (Brown, 1975). An explication of the main concepts of the system is provided along with reinterpretation of a variety of reading research. Analysis of strategic demands and the factors affecting strategic behavior yield a framework for conceptualizing the development of reading fluency. Implications of this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although there is not a specific theoretical framework to define reading comprehension strategies (National Reading Panel, 2000), prior research in reading intervention suggested many evidence-based reading comprehension strategies. Most commonly used strategies for struggling readers include, but are not limited to, main idea (integrating ideas from the text information in a coherent way; National Reading Panel, 2000; Stevens et al, 2019), inference (integrating information within text and between the text and one’s general knowledge of the topic to understand ideas not explicitly stated in the text; O’Brien et al, 2015), text structure (recognizing the underlying structure of texts to help focus attention on key concepts and relationships, anticipate what is to come, and monitor their comprehension as they read; Hebert et al, 2016), retell (organizing information in order to provide a personal rendition of the text; Reed & Vaughn, 2012), prediction (utilizing what is already known from the text and background knowledge to hypothesize the content of the text and evaluate this hypothesis with the actual content; Nolan, 1991), self-monitoring (monitoring the understanding of the text through ways such as self-questioning and coherence check; Schwartz, 1997), and graphic organizers (making graphic representations of the material to assist comprehension; Merkley & Jefferies, 2000). In the current study, we focused on these strategies as they were the ones studied most in the reading comprehension interventions for older, at-risk readers (Filderman et al, 2021; Gersten et al, 2001; Hall, 2016).…”
Section: Theoretical Framework and Practice Considerationsmentioning
confidence: 99%
“…Although there is not a specific theoretical framework to define reading comprehension strategies (National Reading Panel, 2000), prior research in reading intervention suggested many evidence-based reading comprehension strategies. Most commonly used strategies for struggling readers include, but are not limited to, main idea (integrating ideas from the text information in a coherent way; National Reading Panel, 2000; Stevens et al, 2019), inference (integrating information within text and between the text and one’s general knowledge of the topic to understand ideas not explicitly stated in the text; O’Brien et al, 2015), text structure (recognizing the underlying structure of texts to help focus attention on key concepts and relationships, anticipate what is to come, and monitor their comprehension as they read; Hebert et al, 2016), retell (organizing information in order to provide a personal rendition of the text; Reed & Vaughn, 2012), prediction (utilizing what is already known from the text and background knowledge to hypothesize the content of the text and evaluate this hypothesis with the actual content; Nolan, 1991), self-monitoring (monitoring the understanding of the text through ways such as self-questioning and coherence check; Schwartz, 1997), and graphic organizers (making graphic representations of the material to assist comprehension; Merkley & Jefferies, 2000). In the current study, we focused on these strategies as they were the ones studied most in the reading comprehension interventions for older, at-risk readers (Filderman et al, 2021; Gersten et al, 2001; Hall, 2016).…”
Section: Theoretical Framework and Practice Considerationsmentioning
confidence: 99%